Tension-Free Golf : Unleashing Your Greatest Shots More Often - Reinmuth, Dean (Chicago Triumph Books, 2003)
With new chapters on the short game and trouble shots, this classic golf book is a must-have for beginning golfers as well as more experienced players who want to improve. Dean Reinmuth counts among his celebrity students President Gerald Ford.
Include Illustration
Keywords: Golf -- Golf--Psychological aspects